What is new in asthma? - Jassem, Anna; Siemińska, Alicja (Przewodnik Lekarza/Guide for GPs, 2006)
Better understanding of mechanisms involved in asthma enabled the introduction of the new drugs of targeted therapy. Some of them are reviewed in this article.